Urban development and property management in the context of societal transformations: Strategic decision‐making - Melnikas, Borisas (International Journal of Strategic Property Management, 2010)
The urgent problems of urban development and strategic property management in the context of economic, social, political transformations in the society are analyzed. The possibilities of multicriteria strategic decision‐making are described. The following objects are analyzed: urban development under the conditions of transformations as a major research object in the area of strategic property management; cities and their development as an environment of property creation and accumulation; transformation processes as general context of the urban development and of the creation and accumulation of property; the major trends of the transformation processes in Central and Eastern Europe, the main criteria and indicators of them; the evaluation criteria used in the area of urban development and property strategic management in the conditions of transformation processes; multicriteria decision‐making in the area of urban development and property strategic management.First Published online: 18 Oct 2010